Study of affordability of pharmaceutical provision for type 2 diabetes therapy in Ukraine - Vlasenko, I.O.; Gladyshev, V.V.; Zaliska, O.M.; Davtian, L.L. (Medicni Perspektivi, 2025)
Increasing the availability and affordability of medical and pharmaceutical care to the population is the most important task of all levels of government. The purpose of the work is to study the affordability of glucose-lowering drugs for the treatment of type 2 diabetes in Ukraine. Research materials are: State Register of Medicinal Products and price of glucose-lowering drugs. Marketing, analytical, graphic and pharmacoeconomic analysis were used. On the pharmaceutical market of Ukraine 161 glucose-lowering drugs are registered, which contain 16 international non-proprietary names and 8 international non-proprietary names combinations. It was established that the cost of Defined Daily Dose for mono glucose-lowering drugs varies from UAH 1,1 for glibenclamide up to UAH 90,7 for liraglutide. Most of the Ukrainian-made and foreign drugs are highly affordable, but foreign preparations of modern groups are moderately affordable, only one foreign drug, Liraglutide, is unaffordable ratio. But the analysis of affovailability for pensioners only metformin (Ukrainian production), glibenclamide, gliclazide, and glimepiride are highly affordable, three of which are already subject to reimbursement. Modern glucose-lowering drugs, both of foreign and Ukrainian production, is scarcely affordable, which makes it practically impossible to use them in the majority of retirees with diabetes. Thus, the analysis showed that in order to implement modern treatment schemes for type 2 diabetes, which according to the current legislation can be used in Ukraine, it is necessary to expand the list of glucose-lowering drugs included in the reimbursement program. This will improve treatment results, which in turn will reduce the development of diabetes complications and improve the quality of life of patients.